2022
DOI: 10.1002/jbt.23244
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic mechanisms of triclosan: The antimicrobial agent emerging as a toxicant

Abstract: Several scientific studies have suggested a link between increased exposure to pollutants and a rise in the number of neurodegenerative disorders of unknown origin. Notably, triclosan (an antimicrobial agent) is used in concentrations ranging from 0.3% to 1% in various consumer products. Recent studies have also highlighted triclosan as an emerging toxic pollutant due to its increasing global use. However, a definitive link is missing to associate the rising use of triclosan and the growing number of neurodege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 114 publications
0
0
0
Order By: Relevance
“…5 A and B). To further verify the mechanism of how guanine and ADP improved L. plantarum ATCC14917 activity against ROS, triclosan was used to promote intracellular production of ROS [ 58 , 59 ]. The results showed that after the addition of triclosan, survival rates of L. plantarum ATCC14917 decreased by approximately two-fold in the presence of metabolites and antibiotics (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 A and B). To further verify the mechanism of how guanine and ADP improved L. plantarum ATCC14917 activity against ROS, triclosan was used to promote intracellular production of ROS [ 58 , 59 ]. The results showed that after the addition of triclosan, survival rates of L. plantarum ATCC14917 decreased by approximately two-fold in the presence of metabolites and antibiotics (Fig.…”
Section: Resultsmentioning
confidence: 99%